2009
DOI: 10.1016/j.leukres.2008.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and clinical experience with dasatinib in philadelphia chromosome-negative leukemias and myeloid disorders

Abstract: Recent advances in the molecular characterization of Philadelphia chromosome-negative (Ph−) leukemias and related myeloid disorders have provided a clear rationale for investigating novel targeted therapies. Dasatinib is a tyrosine kinase inhibitor with activity against BCR-ABL, platelet-derived growth factor receptors (PDGFRs), c- KIT, fibroblast growth factor receptors (FGFRs), SRC family kinases (SFKs), and EPHA receptors, all of which have been implicated in the pathogenesis of Ph− leukemias and myeloid di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
(91 reference statements)
0
2
0
1
Order By: Relevance
“…Results showed dasatinib to induce a greater percentage LDH release in both 2 and 5 µM concentrations tested compared to imatinib; this trends with the relative drug potencies as dasatinib binds about 325 times stronger than imatinib. 15 This mixed view was supported by a later follow-up study using the same neonatal rat cardiomyo-cyte model, again identifying poor selectivity among TKIs as a driver for damage, and also pointing to the potency of on-target ABL1 inhibition as a simultaneous contributor. 16 It has long been theorized that on-target inhibition of the ABL protein can be a cause of TKI-induced cardiotoxicity, when such adverse effects were seen in clinical trials with imatinib.…”
Section: Selected Tkismentioning
confidence: 94%
“…Results showed dasatinib to induce a greater percentage LDH release in both 2 and 5 µM concentrations tested compared to imatinib; this trends with the relative drug potencies as dasatinib binds about 325 times stronger than imatinib. 15 This mixed view was supported by a later follow-up study using the same neonatal rat cardiomyo-cyte model, again identifying poor selectivity among TKIs as a driver for damage, and also pointing to the potency of on-target ABL1 inhibition as a simultaneous contributor. 16 It has long been theorized that on-target inhibition of the ABL protein can be a cause of TKI-induced cardiotoxicity, when such adverse effects were seen in clinical trials with imatinib.…”
Section: Selected Tkismentioning
confidence: 94%
“…Позитивное по FIP1L1-PDGFRА миелопролиферативное заболевание с эозинофилией ленный в литературе опыт использования этого препарата при МПЗ с эозинофилией [31,32], с 21.11.2012 г. начали терапию дазатинибом в дозе 140 мг/сут. Выбор препарата определялся также значительно большей активностью дазатиниба в отношении PDGFRA-тирозинкиназы по сравнению как с иматинибом, так и с нилотинибом: по неопубликованным данным A. Reiter, ингибирующая концентрация дазатиниба составляет 2,9 нМ против 72 нM для иматиниба и 75 нM для нилотиниба.…”
Section: терапевтический архив 12 2015unclassified
“…This study indicated that dasatinib effectively inhibits Src kinase activity and downstream signalling pathways in CML progenitors, but does not induce a strong proapoptotic response. 87 Several preclinical and clinical studies (extensively reported elsewhere [88][89][90] ) culminated with the FDA approval (June 28, 2006) of dasatinib (SprycelTM). This drug is specifically indicated to treat adults with CP, AP, or myeloid or lymphoid blast phase (MB or LB) CML with resistance or intolerance to prior therapy, including imatinib mesylate.…”
Section: A Thiazole-carboxamides (Dasatinib)mentioning
confidence: 99%